(untitled) (Communications in Mathematical Research, 2021)
Weighted estimates with general weights are established for the maximal operator associated with the commutator generated by singular integral operator and BMO function on spaces of homogeneous type, where the associated kernel satisfies the Hölder condition on the first variable and some condition which is fairly weaker than the Hölder condition on the second variable.